The Effect of Raw Materials on The Quality of Hand-Drawn Batik - Vira Ariestanti Waruwu; Serniati Zebua Zebua; Marta S.D. Mendrofa; Tiarni Duha (Golden Ratio of Data in Summary, 2024)
This research aims to analyze factors that influence the quality of written batik products at CV. Wery Group Gunungsitoli, North Sumatera, Indonesia, North Sumatera, Indonesia. Product quality is an important element that can influence consumer satisfaction and loyalty. This research uses a quantitative approach with survey methods. Data was collectod throught a questionnaire distributed to cosumers of the CV. Wery Group Gunungsitoli, North Sumatera, Indonesia. The variables studied include raw materials, craftsmen’s skills, production techniques, and quality management. Data analysis was carried out using SPSS software with multiple linear regression tests to determine the effect of each variable on product quality. The research result show that raw materials, craftsmen’s skills, have asignificant influence on the quality or written batik products. Production techniques and quality management also have a positive influence, althougt not as much as the other two factors. The conclusion of this research is that CV. Wery Group Gunungsitoli, North Sumatera, Indonesia needs to pay attention to the selection of quality raw materials and improve the skills of craftsmen to improve the quality of written batik products. It is hoped that this research can contribute to the development of the written batik industry in Gunungsitoli and become a reference for companies in efforts to improve product quality.